Transverse rectus abdominis myocutaneous flap coverage for orbital defect after post-traumatic enucleation: a case report - Chang, Emiliano O.; Renteria, Jorge M. M.; Escamilla, Manuel E. de la O.; Campo, Rafael R. (International Journal of Research in Medical Sciences, 2025)
A 72-year-old male presented with a chronic, unhealed wound in the left orbital socket following a left eye enucleation due to a traumatic injury sustained 15 years prior. The patient’s condition stemmed from a puncture wound that led to significant complications and subsequent orbital defect. Surgical intervention involved the use of a transverse rectus abdominis myocutaneous (TRAM) flap for reconstruction. It includes flap elevation from the abdominal wall, vascular anastomosis between the facial artery and the deep inferior epigastric artery, and inset of the flap into the orbital defect. The surgery was completed without complications, and the patient experienced satisfactory recovery. This case underscores the effectiveness of utilizing a TRAM flap for reconstructing orbital defects following exenteration and highlights the importance of individualized surgical strategies in managing complex facial reconstructive challenges.